Latin American Poetry: Intersections, Translations, Encounters - Stahl, Henrieke; Korte, Hermann; Masumoto, Hiroko; Sandler, Stephanie (PH02, 2024)
This volume of “Neuere Lyrik” contains a selection of texts on Latin American poetry that focuses on its encounter – at times direct and dialogic; at times indirect or even oppositional – with foreign texts and traditions. The question it therefore raises is what constitutes the borders – cultural, medial, discursive, linguistic, etc. – of a poetic tradition to begin with, particularly today. While each text replies uniquely, their approaches can be broadly assigned to three distinct areas of inquiry: transcultural and transhistorical discourse; intermedial experimentation; and translation. Their attention to these liminal modes, moreover, prompts a remapping of poetry itself by asking how, in continually becoming foreign to itself, poetry is returned to its proper home.
Peter Lang GmbH, Internationaler Verlag der Wissenschaften